The Impact of Welfare State to Labour Market. European Submodels Differences - Cristian SOCOL; Marius MARINAŞ; Aura-Gabriela SOCOL (Theoretical and Applied Economics, 2010)
In this study, we show the effects which the measures to implement welfare state have to labour market. All knows that the employment represents the most important component of the welfare state, as it supports the fulfillment of the objectives for the economic and social policies. The argument of the previous statement is very simple: the expenses for social protection are made on the basis of the returns from taxes and social contributions paid by the employed persons. The higher their number, the bigger the tax basis, and the budget for the social policy will become sustainable, even though measures for decreasing taxation would be applied to companies and to the employed population. The entire virtuous mechanism may disintegrate if a low rate of employment persists. In case of a high unemployment on a long-term, of an early exit from the labour market, of a lower integration on the labour market of women, of young persons, of aged persons and of poorly qualified persons, the social expenses will increase and the budget revenues will decrease, the result being the increase in the state’s debt.The crisis will prove whether the increase in employment recorded since 2000 was conjunctural (determined by the favorable macroeconomical evolutions) or structural (induced by the reforms implemented on the labour markets and in the social protection systems).